Manual segmentation qualification platform for the EADC‐ADNI harmonized protocol for hippocampal segmentation project. Issue 2 (21st January 2015) - Duchesne, Simon; Valdivia, Fernando; Robitaille, Nicolas; Mouiha, Abderazzak; Valdivia, F. Abiel; Bocchetta, Martina; Apostolova, Liana G.; Ganzola, Rossana; Preboske, Greg; Wolf, Dominik; Boccardi, Marina; Jack, Clifford R.; et al.
Abstract: Background: The use of hippocampal volumetry as a biomarker for Alzheimer's disease (AD) requires that tracers from different laboratories comply with the same segmentation method. Here we present a platform for training and qualifying new tracers to perform the manual segmentation of the hippocampus on magnetic resonance images (MRI) following the European Alzheimer's Disease Consortium and Alzheimer's Disease Neuroimaging Initiative (EADC‐ADNI) Harmonized Protocol (HarP). Our objective was to demonstrate that the training process embedded in the platform leads to increased compliance and qualification with the HarP. Method: Thirteen new tracers' segmentations were compared with benchmark images with respect to: (a) absolute segmentation volume; (b) spatial overlap of contour with the reference using the Jaccard similarity index; and (c) spatial distance of contour with the reference. Point by point visual feedback was provided through three training phases on 10 MRI. Tracers were then tested on 10 different MRIs in the qualification phase. Results: Statistical testing of training over three phases showed a significant increase of Jaccard (i.e. mean Jaccard overlap P  < .001) between phases on average for all raters, demonstrating that training positively increased compliance with the HarP. Based on these results we defined qualification thresholds which all tracers were able to meet. Conclusions: This platform is an adequate infrastructure allowing standardized training and evaluation of tracers' compliance with the HarP. This is a necessary step allowing the use of hippocampal volumetry as a biomarker for AD in clinical and research centers.